Neurologic deficit due to vertebral body osteophytes after oblique lumbar interbody fusion: A case report. Issue 50 (17th December 2021) - Lee, Tae-Kyu; Kim, Jae-Young; Han, Moon-Soo; Lee, Jung-Kil; Moon, Bong Ju
Abstract: Rationale: In recent years, oblique lumbar interbody fusion (OLIF), which uses a window between the peritoneum and the iliopsoas muscle to split the muscle to access the lumbar spine, is known as an effective and safe treatment for spinal diseases, such as degenerative disc disease, spondylolisthesis, recurrent disc herniation, and spinal deformity. Despite this fast and useful surgical method, there were often cases of new neurological symptoms or worsening of symptoms after surgery. We analyzed the preoperative risk factors in a patient with neurologic symptoms, such as motor weakness and exacerbation of radiating pain, after OLIF. Patient concerns: A 78-year-old man presented with complaints of numbness in the soles of both feet. L4–5 stenosis was diagnosed on MRI. We performed bilateral L4 laminotomy and L4–5 percutaneous posterior screw fixation after L4–5 OLIF. Postoperatively, his radiating pain improved, and there were no other neurologic symptoms. In the 6th week after surgery, he complained of pain in both ankles, while in the 10th week, the pain progressively worsened, and there was a decrease in motor performance of the right ankle. Diagnosis: Magnetic resonance imaging findings indicated that L4–5 stenosis was resolved. On the basis of the computed tomography findings, the cage was well inserted, the disc height and foramen height increased, and the alignment was good. However, a nerve root injury due to the protruding osteophyte from the inferior endplate of the L4 body was suspected, necessitating exploration of both L4 nerve roots by focusing on the right side. Interventions: We performed right facetectomy and right foraminotomy. During surgery, it was confirmed that the right L4 nerve root was entrapped by the osteophyte. Outcomes: Postoperatively, his radiating pain improved, and motor performance of his right ankle was restored. Lessons: A prominently protruding osteophyte is assessed as a possible risk factor for the development of new neurologic deficits after OLIF. In patients with confirmed osteophytes, surgery should be planned taking into consideration the shape of the osteophytes and their relationship to the nerve root.